Downregulation of the zinc transporter SLC39A13 (ZIP13) is responsible for the activation of CaMKII at reperfusion and leads to myocardial ischemia/reperfusion injury in mouse hearts. (March 2021) - Wang, Jie; Cheng, Xinxin; Zhao, Huanhuan; Yang, Qing; Xu, Zhelong
Abstract: While Zn 2+ dyshomeostasis is known to contribute to ischemia/reperfusion (I/R) injury, the roles of zinc transporters that are responsible for Zn 2+ homeostasis in the pathogenesis of I/R injury remain to be addressed. This study reports that ZIP13 (SLC39A13), a zinc transporter, plays a role in myocardial I/R injury by modulating the Ca 2+ signaling pathway rather than by regulating Zn 2+ transport. ZIP13 is downregulated upon reperfusion in mouse hearts or in H9c2 cells at reoxygenation. Ca 2+ but not Zn 2+ was responsible for ZIP13 downregulation, implying that ZIP13 may play a role in I/R injury through the Ca 2+ signaling pathway. In line with our assumption, knockout of ZIP13 resulted in phosphorylation (Thr 287 ) of Ca 2+ -calmodulin-dependent protein kinase (CaMKII), indicating that downregulation of ZIP13 leads to CaMKII activation. Further studies showed that the heart-specific knockout of ZIP13 enhanced I/R-induced CaMKII phosphorylation in mouse hearts. In contrast, overexpression of ZIP13 suppressed I/R-induced CaMKII phosphorylation. Moreover, the heart-specific knockout of ZIP13 exacerbated myocardial infarction in mouse hearts subjected to I/R, whereas overexpression of ZIP13 reduced infarct size. In addition, knockout of ZIP13 induced increases of mitochondrial Ca 2+, ROS, mitochondrial swelling, decrease in the mitochondrial respiration control rate (RCR), and dissipation of mitochondrial membrane potential (Δ Ψ m) in a CaMKII-dependent manner. These data suggest that downregulation of ZIP13 at reperfusion contributes to myocardial I/R injury through activation of CaMKII and the mitochondrial death pathway. Highlights: ZIP13 is downregulated at reperfusion in mouse hearts. Downregulation of ZIP13 leads to CaMKII activation. The heart-specific knockout of ZIP13 exacerbated myocardial infarction via CaMKII in mouse hearts subjected to I/R. Knockout of ZIP13 induced mitochondrial damage in a CaMKII-dependent manner.